Implementasi Sistem Back Up Jalur Data (Load Balance And Failover) 2 ISP Dengan Metode Per-Connection Classifier Berbasis Mikrotik - Misbah Hudaini , Ahmad; Islamiyah, Mufidatul (JURNAL SISTEM KOMPUTER ASIA, 2024)
This study discusses the implementation of a data line back-up system (load balance and failover) for 2 ISPs with a proxy-based per-connection classifier method, with this study displaying measurement results when the network in Himakost experiences slow, disconnected problems and the solution. In this study, based on the existing constraints, the load balance process was carried out using the per-conncetion classifier method whose function was to balance traffic and overload loads and failover whose function was to backup data. From the results of the sampling test for each of the 5 data from the load balance, it can be seen that the results of the comparison of traffic and overload monitoring between ISP-1 and ISP-2 and their combination have significant changes, this shows that the application of load balance in Himakost is running well. . As for failover testing, testing is carried out by disconnecting each ISP with the aim of backing up data and proving its success.